2017
DOI: 10.1002/mame.201700135
|View full text |Cite
|
Sign up to set email alerts
|

Direct Printing of Thermal Management Device Using Low‐Cost Composite Ink

Abstract: This work presents a new method for fabricating thermal devices, such as heat sinks, using a 3D printing technique and lightweight composite ink. The method focuses on formulating composite inks with desired properties and direct ink writing for manufacturing. The ink undergoes two phases: phase one uses low viscosity epoxy to provide viscoelastic properties and phase two provides the fillers consisting of carbon fiber and graphite nanoplatelets to provide high thermal conductivity and structural properties. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…Ink materials used by direct write printing are typically formulated and designed to rapidly solidify after exiting the nozzle tip. [13,21,35] Figure 1a and b represent desired rheological properties of ink used for direct ink printing, which was formulated by Lewis and coworkers. Various building block materials can be used for direct write printing ranging from ceramics, polymers, to composites.…”
Section: Direct Write Printing Techniquesmentioning
confidence: 99%
See 4 more Smart Citations
“…Ink materials used by direct write printing are typically formulated and designed to rapidly solidify after exiting the nozzle tip. [13,21,35] Figure 1a and b represent desired rheological properties of ink used for direct ink printing, which was formulated by Lewis and coworkers. Various building block materials can be used for direct write printing ranging from ceramics, polymers, to composites.…”
Section: Direct Write Printing Techniquesmentioning
confidence: 99%
“…Examples of hybrid fillers include graphene oxide and carbon nanotubes (CNTs) [37] or mixtures of silver nanowires and CNTs. [13] The authors reported that the composites offered a thermal conductivity of 2 W m À1 K À1 , and the ink can be used to print heat sinks or thermal interface materials. [13] The authors reported that the composites offered a thermal conductivity of 2 W m À1 K À1 , and the ink can be used to print heat sinks or thermal interface materials.…”
Section: Direct Write Printing Techniquesmentioning
confidence: 99%
See 3 more Smart Citations